A label-free aptasensor for clenbuterol detection based on fluorescence resonance energy transfer between graphene oxide and rhodamine B. Issue 50 (15th November 2022) - Xiao, Shuyan; Sun, Liang; Kang, Mingqin; Dong, Zhongping
Abstract : A label-free aptasensor for clenbuterol was developed through the fluorescence resonance energy transfer mechanism by using an aptamer as the recognition element, rhodamine B as the fluorescence probe and graphene oxide as the fluorescence quencher. Abstract : A novel label-free aptasensor for the specific detection of clenbuterol was developed through the fluorescence resonance energy transfer (FRET) mechanism by using an aptamer as the target recognition element, rhodamine B (RhoB) as the fluorescence probe and graphene oxide (GO) as the fluorescence quencher. In the absence of clenbuterol, the aptamer was adsorbed on the surface of GO, preventing the interaction between RhoB and GO, and a high fluorescence signal was obtained. In the presence of clenbuterol, the aptamer specially bound to clenbuterol with a high affinity and detached from the surface of GO, while positively charged rhodamine B could be electrostatically adsorbed onto the surface of GO, thus quenching the fluorescence. By comparing the fluorescence intensity before and after the addition of clenbuterol, a simple and fast fluorescence assay for clenbuterol was established with a detection range of 100–700 nM and a detection limit of 9.6 nM. Moreover, the proposed method was successfully applied in the determination of clenbuterol in pork samples with recoveries in the range of 96.75–104.91% and a relative standard deviation of less than 5.67%. Because of its easy operation, fast response, low cost and competitive analytical performance, this method is a promising candidate for the detection of clenbuterol and can be extended to the detection of other targets by changing the corresponding aptamers.